REGULATION OF THE USE OF FOREIGN WORKERS IN INDONESIA AFTER THE JOB CREATION ACT: PROBLEMS AND SOLUTIONS - Ayu Putri Rainah Petung Banjaransari (Fakultas Hukum Universitas Lampung, 2022)
Problems in the labor law sector in Indonesia cannot be separated from the increasing number of foreign workers which are feared to take the place and role of domestic workers. This problem almost always exists every year because foreign investment enters Indonesia while bringing in foreign workers as expert workers or genuine workers from the investors' countries of origin. The entry of foreign workers is a trigger for disputes between foreign workers and domestic workers. As it is known that the Indonesian population is very large, which can be seen from the annual data of the national statistical center, while the high population is not matched by a large number of jobs, resulting in unemployment and regional economic inequality. Based on this background, the problem of foreign workers is related to the renewal of the Law of the Republic of Indonesia Number 11 of 2020 concerning Job Creation (herein after referred to as the Job Creation Law) and its implementing regulations. This paper uses a normative legal research method using legal sources from secondary legal materials. This legal research uses a legal and conceptual approach with a focus on regulations and concepts or theories or principles related to the research topic. This paper presents problems in the new regulation on foreign workers after the enactment of the Job Creation Law. In addition, this paper presents its solution efforts to overcome these problems in Indonesia. This paper uses a normative legal research method using legal sources from secondary legal materials. This legal research uses a legal and conceptual approach with a focus on regulations and concepts or theories or principles related to the research topic. This paper presents problems in the new regulation on foreign workers after the enactment of the Job Creation Law. In addition, this paper presents its solution efforts to overcome these problems in Indonesia. This paper uses a normative legal research method using legal sources from secondary legal materials. This legal research uses a legal and conceptual approach with a focus on regulations and concepts or theories or principles related to the research topic. This paper presents problems in the new regulation on foreign workers after the enactment of the Job Creation Law. In addition, this paper presents its solution efforts to overcome these problems in Indonesia.